Pendidikan dan Perubahan Sosial Masyarakat Pedesaan di Minahasa - J. Rompas (Antropologi Indonesia, 1995)
The author explains how social change occurred in Minahasa due to education. Traditional education in Minahasa was strongly influenced by traditional belief (malesung) in which the teachers were adat leaders called walian. The impacts of Western education were felt with the arrival of the Spanish and Portuguese in the 16th century. In the middle of the 17th century both of them were expelled by the Dutch. VOC and NZG intensively disseminated Protestantism with the founding of schools for teachers, assistant preachers, and elementary schools. Those schools resulted into the decline of agricultural skills and handicraft of the youth which had been the primary way of earning a livelihood. They tend to look for work outside their villages. After independence, education grew rapidly with the increase of the number of schools. However, the awareness of the importance of education in some rural areas was not accompanied with the increase of social welfare.